Influence of soft skills, and employee productivity, on organizational performance, a developing field: current state and relationship - Fernando Andrés Muñoz-Peña; Jason Steve Pulido-Reina (Dyna)
Soft skills and employee productivity are key factors in sustainability and corporate performance in competitive and dynamic environments. The purpose of this article is to identify current findings related to soft skills, employee productivity and their relationship with organizational performance, and to propose a structural model that allows establishing this relationship. The results of some research conducted individually reveal positive and significant relationships in the proposed fields. Some skills found in the literature are communication, problem solving and decision making. To carry out this research, multiple research papers were collected between 2005 and 2024. A structural equation model was used as a way to propose a relationship between the aforementioned factors. This research theoretically demonstrated that soft skills and employee productivity contribute positively and significantly to organizational performance. Limitations may arise depending on the particularities of the industrial sector and the economic context. Since there is little research in the analyzed fields, this study contributes significantly to the identification of key variables.